What Is the Role of AI in Dementia Care? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Dementia, a neurodegenerative condition characterized by a progressive decline in cognitive function, represents one of the most significant global health ch...
Keywords: AI in Geriatrics; Dementia; Care; Artificial Intelligence; Machine Learning; Deep Learning; Healthcare